Outcomes of a bedside ultrasound-guided peripherally-inserted central catheter placement across critically-ill older patients - Kyungwon Lee; Kyoung Won Yoon; Minchang Kang; Donghyoun Lee (PLoS ONE, 2026)
Background An ultrasound (US)-guided peripherally inserted central catheter (PICC) is a thin, flexible tube inserted into a vein in the upper arm and then guided into a large vein near the heart, using US for precise vein location. We conducted this single-center, retrospective study to describe outcomes of a bedside US-guided PICC across critically-ill older patients in a single small-volume center in an intensive care unit (ICU) setting in Korea. Methods We included 452 Korean older ICU patients aged ≥60 years who received PICC at our hospital between January of 2021 and December of 2024. A logistic regression analysis with odds ratio (OR) was performed to identify risk factors of the non-optimal position of catheter tip. The overall PICC-related infection-free survival was expressed as mean±standard error, for which 95% confidence intervals (CIs) were provided and the statistical significance was analyzed using the log-rank test. The corresponding Kaplan-Meier survival and hazards were plotted as a curve. Results There were a total of 13 cases (2.88%) of the PICC-related infection. Of these, there were five cases (1.1%) of PICC-related bloodstream infection. A total of 421 patients (93.1%) had optimal positions of the PICC tip. A logistic regression analysis showed that male sex (OR 0.202; 95% CI 0.078–0.521, p = 0.001), the length of a catheter (OR 0.786; 95% CI 0.683–0.904, p = 0.001) and right side (OR 4.415; 95% CI 1.649–11.824, p = 0.003) were significant risk factors of non-optimal positions of the catheter. Time-to-events are estimated at 56.29 ± 0.98 days (95% CI 54.37–58.21). Moreover, survival rates are estimated to reach 0.918 ± 0.032 (95% CI 0.858–0.983) at 31 days of the PICC use. Conclusions We describe outcomes of a bedside US-guided PICC across critically-ill older patients in a single small-volume center in an ICU setting in Korea.